Bhumi Bhaban : Satrastar Mor, Tejgaon, Dhaka - Thoiba, Kongkham Parihan (BRAC Univeristy, 2017)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Architecture, 2016.